The virtual network city and the long-tail of social media alienation - Christopher, David (Svetovi (Ljubljana), 2025)
Castells’ fundamental first volume of his Information Age trilogy entitled The Rise of the Network Society (1996) significantly overlooks the social phenomena that comprise and lead back to insularisation in online networks and abroad. As the call for this special issue notes, “the world we live in today is characterised by high levels of interconnectivity, codependence, and overwhelming amounts of information”, which “shapes our desires” and “evokes ideas of isolation, remoteness, and detachment from everyday worries.” (Oroz and Simonič2023) Unfortunately, these often unconscious desires to disconnect from McLuhan’s celebrated “global village” and Jameson’s unsavory “junkspace”, as repressed desires, may manifest as anti-social sentiments that develop longitudinally under the conditions of what I theorise as the virtual network city.
Keywords: alienation; digital environment; digitalno okolje; družbeni mediji; insularisation; izolacija; network city; odtujenost; omrežno mesto; social anthropology; social media; social networks; socialna antropologija; socialna omrežja